NUTRICHARGE – BIODEGRADABLE POLYMER TO PROLONG THE ACTION OF PHOSPHOROUS AND MINERAL FERTILIZERS IN THE SOIL - S. M. Khromov (Ovoŝi Rossii, 2017)
We pose a problem of low efficiency of complicated mineral fertilizers, phosphorus fixation by metals and its inaccessibility for plants during the season.